1998
DOI: 10.1021/cr980011z
|View full text |Cite
|
Sign up to set email alerts
|

Metal Oxide Surfaces and Their Interactions with Aqueous Solutions and Microbial Organisms

Abstract: previously he was at Sandia National Laboratories. His research concerns the energetics and kinetics of the reactions between minerals and aqueous solutions, and in recent work, he has determined rate coefficients for dissociation of Al−O bonds in various dissolved aluminum complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

25
847
1
7

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,001 publications
(883 citation statements)
references
References 702 publications
25
847
1
7
Order By: Relevance
“…At the same time, this also indicated that the reactive velocity of reaction (3) was neither much slower (as MgO 2 ) nor much faster (as BaO 2 ) than that of reaction (2) for CaO 2 . The exhibited disciplinarian from MgO 2 to CaO 2 to BaO 2 might rest with the metal and crystal lattice properties of the alkaline-earth metal peroxides as metal oxides (36), which needs further investigation in the future.…”
mentioning
confidence: 99%
“…At the same time, this also indicated that the reactive velocity of reaction (3) was neither much slower (as MgO 2 ) nor much faster (as BaO 2 ) than that of reaction (2) for CaO 2 . The exhibited disciplinarian from MgO 2 to CaO 2 to BaO 2 might rest with the metal and crystal lattice properties of the alkaline-earth metal peroxides as metal oxides (36), which needs further investigation in the future.…”
mentioning
confidence: 99%
“…Because the dimensions of nanomaterials are only a fraction of the space charge layer thickness in solid materials, screening effects from electrolytes and specifically adsorbed ions are dominant. For pure water, the most important ions are hydroxide and hydronium ions, and their effect on metal oxides, including TiO 2 [106] and Fe 2 O 3 [107,108] gives rise to the well-known 59 mV pH À1 variation of the flatband potential with the solution pH [109]. In surface water, phosphate, silicate, and fluoride ions are often strongly adsorbing [110], which determines the redox stability of many minerals [109].…”
Section: Multiple Exciton Generationmentioning
confidence: 99%
“…For pure water, the most important ions are hydroxide and hydronium ions, and their effect on metal oxides, including TiO 2 [106] and Fe 2 O 3 [107,108] gives rise to the well-known 59 mV pH À1 variation of the flatband potential with the solution pH [109]. In surface water, phosphate, silicate, and fluoride ions are often strongly adsorbing [110], which determines the redox stability of many minerals [109]. In contrast, the flatband potentials of II/VI, III/V, and group IV semiconductors are more susceptible to adsorption of soft ligands, including sulfur [111], HS À [112,113], HTe À [114,115], and Cl À [116].…”
Section: Multiple Exciton Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of mesoporous membrane type film with large surface areas prepared from nanosized colloidal semiconductor dispersion caused a remarkable growth in the field (Brown Jr. et al 1999). Dye sensitization of nanostructured wide band-gap semiconductors has led to an extension of their photoresponse into the visible region and to efficient conversion of solar energy into electricity in photoelectrochemical devices (O'Reagan & Grätzel 1991).…”
Section: Solar Cellsmentioning
confidence: 99%